2018
DOI: 10.1021/acs.bioconjchem.8b00684
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Reducing Conditions Enable Conjugation of Oxidized Peptides to Polymers by One-Pot Thiol Click Chemistry

Abstract: Thiol­(-click) chemistry has been extensively investigated to conjugate (bio)­molecules to polymers. Handling of cysteine-containing molecules may however be cumbersome, especially in the case of fast-oxidizing coiled-coil-forming peptides. In the present study, we investigated the practicality of a one-pot process to concomitantly reduce and conjugate an oxidized peptide to a polymer. Three thiol-based conjugation chemistries (vinyl sulfone (VS), maleimide, and pyridyldithiol) were assayed along with three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Reducing the disulfide bond could theoretically reactivate the Cys-Kcoil, but we observed that reducing agents deactivated the functional groups of the linkers typically used to perform the thiol chemistry . Hence, reversing the oxidation to subsequently perform the grafting is not practically feasible.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Reducing the disulfide bond could theoretically reactivate the Cys-Kcoil, but we observed that reducing agents deactivated the functional groups of the linkers typically used to perform the thiol chemistry . Hence, reversing the oxidation to subsequently perform the grafting is not practically feasible.…”
Section: Discussionmentioning
confidence: 98%
“…33 Reducing the disulfide bond could theoretically reactivate the Cys-Kcoil, but we observed that reducing agents deactivated the functional groups of the linkers typically used to perform the thiol chemistry. 34 Hence, reversing the oxidation to subsequently perform the grafting is not practically feasible. Therefore, producing a Kcoil that is devoid of any cysteine residue (Cys-free Kcoil) would be preferable as there would be no need to monitor/control the oxidation level, rendering large-scale production in a bioreactor possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEE and 10% PLA- b -PEG-maleimide NPs were incubated (1000:1 molar ratio) overnight in 100 mM saline phosphate buffer (pH 7.4) in the presence of the reducing agent tris­(2-carboxyethyl)­phosphine (TCEP, 100:1 TCEP/CEE molar ratio) for the reduction of disulfide bridges that might form between CEE molecules. Previous work in our research group had shown that these reducing conditions prove adequate to promote thiol–maleimide coupling, even when a significant fraction of the cysteine-terminated peptide is oxidized …”
Section: Methodsmentioning
confidence: 99%
“…Previous work in our research group had shown that these reducing conditions prove adequate to promote thiol−maleimide coupling, even when a significant fraction of the cysteine-terminated peptide is oxidized. 58 The samples then underwent three cycles of purification through an Amicon centrifugal filter unit (cutoff 50 kDa, Millipore Sigma #UFC9050). Supernatants were kept for further quantification of the unreacted CEE.…”
Section: X Xmentioning
confidence: 99%